2023
DOI: 10.1007/s00382-023-06672-3
|View full text |Cite
|
Sign up to set email alerts
|

Wet bias of summer precipitation in the northwestern Tibetan Plateau in ERA5 is linked to overestimated lower-level southerly wind over the plateau

Abstract: The Tibetan Plateau (TP), also called the Third Pole, is considered to be “the world water tower”. The northwestern TP (NWTP), which has an average elevation higher than 4800 m, is an arid region where the summer precipitation is largely overestimated by the ERA5 global reanalysis product. We hypothesize that this wet bias is mainly caused by unrealistic lower-level winds that trigger strong convection over the region; it can be reduced by using a high-resolution regional climate model with a large domain that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 86 publications
1
10
0
Order By: Relevance
“…In winter, WVT to the TP mainly comes from the westerly wind belt (X. Liu et al., 2020). Changes in atmospheric circulation can affect the WVT which is critical for the precipitation over the TP (e.g., Lin et al., 2018; Ou et al., 2023). Figure 9a shows the distribution of water vapor flux (WVF) over the TP and in surrounding areas in winter of 2000–2019 in the EXP_KD05 experiment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In winter, WVT to the TP mainly comes from the westerly wind belt (X. Liu et al., 2020). Changes in atmospheric circulation can affect the WVT which is critical for the precipitation over the TP (e.g., Lin et al., 2018; Ou et al., 2023). Figure 9a shows the distribution of water vapor flux (WVF) over the TP and in surrounding areas in winter of 2000–2019 in the EXP_KD05 experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Ou et al. (2023) and P. Zhou et al. (2022) revealed that the wet biases over the TP in the ERA5 global reanalysis can be alleviated by WRF dynamical downscaling simulation at a gray‐zone resolution (9 km), owing to the more realistic representation of low‐level southerlies and WVT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current literature lacks studies with a focus on the link between MCS-associated precipitation, water availability for agriculture and flooding in the river basins around the TP, even though there exist several refined multi-decadal simulations that might be useful for this purpose (Table 4). These include, for instance, the High Asia Refined analysis (HAR; Maussion et al, 2014;Wang et al, 2021c) with a horizontal grid spacing of 10 km and a WRFbased downscaling product with a horizontal grid spacing of 9 km (Ou et al, 2020;2023; Table 4). In addition, a CORDEX Flagship Pilot study named "Convection-Permitting Third Pole" (Prein et al, 2022) has been launched and endorsed by WCRP-CORDEX to coordinate the high-resolution modeling work focusing on MCSs and precipitation over the TP and its downstream regions.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…The fifth-generation ECMWF atmospheric reanalysis of the global climate was downscaled to provide a high-resolution (3 km) temperature and precipitation data set over Southeast Asia using the Weather Research and Forecasting Model version 3.7.1. This data set has been proven to be highly reliable and meets high accuracy requirements (Ou et al, 2020(Ou et al, , 2023.…”
Section: Data Sets and Pre-treatmentmentioning
confidence: 99%